2020
DOI: 10.3390/f11040395
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Water Deficit and Salt Stress in Silver Fir (Abies alba Mill.) Seedlings

Abstract: Forest ecosystems are frequently exposed to abiotic stress, which adversely affects their growth, resistance and survival. For silver fir (Abies alba), the physiological and biochemical responses to water and salt stress have not been extensively studied. Responses of one-year-old seedlings to a 30-day water stress (withholding irrigation) or salt stress (100, 200 and 300 mM NaCl) treatments were analysed by determining stress-induced changes in growth parameters and different biochemical markers: accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 88 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…The results presented here indicate that the patterns of stress-induced changes in antioxidant enzyme activities were the same for the two selected lavender cultivars since, with very few exceptions, no significant differences between LAC and LAS plants were observed in any of the control or stress treatments. Also, no significant increase in any of the enzyme activities has been detected in response to water deficit; in fact, the GR activity even decreased significantly in both lavender varieties, as reported in other species, for example in spruce seedlings (Todea et al, 2020). These data suggest that the antioxidant response to drought in lavender is primary based on the accumulation of phenolic compounds, in general, and of flavonoids, in particular, without involvement of the assayed antioxidant enzyme systems.…”
Section: Discussionsupporting
confidence: 65%
“…The results presented here indicate that the patterns of stress-induced changes in antioxidant enzyme activities were the same for the two selected lavender cultivars since, with very few exceptions, no significant differences between LAC and LAS plants were observed in any of the control or stress treatments. Also, no significant increase in any of the enzyme activities has been detected in response to water deficit; in fact, the GR activity even decreased significantly in both lavender varieties, as reported in other species, for example in spruce seedlings (Todea et al, 2020). These data suggest that the antioxidant response to drought in lavender is primary based on the accumulation of phenolic compounds, in general, and of flavonoids, in particular, without involvement of the assayed antioxidant enzyme systems.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast, the proline of AM plants peaked under 320 mM NaCl, and the value is higher than corresponding NM plants, which showed that AM plants possess stronger resistance. Plants can resist salt stress by accumulating soluble protein and proline, and AMF can effectively alleviate the damage of osmotic metabolism system caused by high concentrations of NaCl ( Dudhane et al, 2011 ; Todea et al, 2020 ). Studies have shown that AMF can maintain a low intracellular osmotic potential and normal cellular metabolism by promoting the accumulation of proline in mycorrhizal plants under salt stress ( Feng et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Salt stress increased DAO and PAO activities in the roots of salt-resistant rice cultivars and in the shoots of saltsensitive ones (Quinet et al 2010). However, the activities of cw-POD and PAO decreased in hyperhydricity of garlic plantlets under oxidative stress treatment (Tian et al 2017). Moreover, cw-POD-dependent and PAO-dependent H2O2 generation was the major source of H2O2 accumulation in the roots of cucumber under salt stress (Wu et al 2018).…”
Section: Discussionmentioning
confidence: 97%